Proposta de modelo de plano de negócios para pequenas empresas em atuação no e-commerce: um estudo de caso - Nogueira, Jedson Oriel de Melo (Universidade Federal Rural do Semi-Árido, 2019)
The present work included is a proposal to elaborate a new business plan model. The work will present the structural model of its composition and its components present in its subsections divided into nine sequential chapters that compose it. Profits will be: Opportunity, One Company, Products and Services Offered, Consumer Market, Environment, Production and Operations, Marketing and Sales, Staff and Finance. Nature research has a large turnover and its applications. The model was developed and developed based on the five reference models associated with e-commerce, exposed to the research result. With the model, a case study will be applied to its results to validate its implementation. Finally, the work should serve as a reference for the study and perspective of future ones
Monografia
Keywords: Plano de Negócios; E-commerce; Empreendedorismo; Modelo; Business plan; E-commerce; Entrepreneurship; Model; ENGENHARIAS::ENGENHARIA DE PRODUCAO